Quality Characteristics and In Vitro Digestibility of Starch Gel in White Noodles Prepared with Short-Chain Glucan Aggregates (SCGA) - Jae-Geun Park; Sang-Jin Ye; Seon-Min Oh; Jae-Sung Shin; Ji-Eun Bae; Hyun-Wook Choi; Moo-Yeol Baik (Gels)
Short-chain glucan aggregates (SCGA), a type of resistant starch (RS) Ⅲ, is produced by debranching amylopectin with pullulanase and inducing self-assembly. Despite its low digestibility and high RS content, SCGA has not been applied to real food systems, especially noodles. The objective of this study was to determine the feasibility of low-digestible noodles using SCGA and to evaluate their quality characteristics and in vitro digestibility of starch gel. SCGA-noodles (SN) were prepared by substituting 0, 10, 20, and 25% of wheat flour with SCGA, and non-digestible maltodextrin (NMD) replaced 7% of the flour for comparison. Adding SCGA increased L- and b-values of the dough, resulting in a brighter appearance, while the NMD increased a-values. The substitution with SCGA weakened the gluten network, reducing dough and texture properties. Notably, cooked SN25 broke immediately in the tensile test, indicating substitution up to 20% is feasible in noodles. NMD7 formed sticky dough and showed extensive elongation without breaking. SN20 and SN25 significantly increased RS content and decreased the estimated glycemic index (eGI) compared to the control. However, NMD7 did not significantly reduce in vitro starch digestibility. In conclusion, this research confirmed the potential of SCGA as a low-digestible ingredient for noodles and other food applications.